The Effect of Discipline and Physical Work Environment on Employee Productivity At PT. Liebra Permana Gunung Putri Bogor - Ading Sunarto; Darmawan Maulana (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to determine the effect of Discipline and Physical Work Environment on Employee Productivity at PT. Liebra Permana Gunung Putri Bogor. The sample in this study is the total number of employees of PT. Liebra Permana Gunung Putri Bogor has as many as 70 employees. The method used in this research is to use a quantitative research approach. The data analysis method in this study uses the IBM SPSS Version 26 application. Based on the results of the validity test of the Work Discipline (X1) variable and the Physical Work Environment variable (X2), the overall value of r count > r table is 0.2352; it can be concluded that all items in the indicator both variables are valid. The results of the multiple linear equation Y= 4.731 + 0.593 X1 + 0, 344 X2 This means that the Work Discipline variable (X1) and the Physical Work Environment variable (X2) in the direction of Work Productivity (Y) have a positive effect. The correlation coefficient of the influence of Work Discipline of 0.724, the Physical Work Environment of 0.688 with an r table of 0.2352. both variables are said to be valid because r count > r table, it is concluded that Work Discipline (X1) and Physical Work Environment (X2) affect Productivity (Y). The coefficient of determination of 0.665 means that the relative contribution given by the combination of variables X1 and X2 to Y is 66.5%, while the remaining 33.5% is influenced by other variables not examined. For the results of the partial test (t-test), the t value of the Work Discipline variable (X1) is 8.666 > 1.996, and the Physical Work Environment (X2) variable is 7.809 > 1.996. It means that there is a significant influence of Work Discipline (X1) and Physical Work Environment (X2) on the Work Productivity (Y) variable, then the hypothesis is accepted. Meanwhile, for simultaneous testing (F test), the calculated F value is 66,357 > 3.13, so H0 is rejected, and Ha is born (influential).